Analysis of Disease in Plants Guava Demspter Shafer Method Using Web Based in the village of Paradise Sei Rampah: Analysis of Disease in Plants Guava Demspter Shafer Method Using Web Based in the village of Paradise Sei Rampah - Adjie Bintang Pamungkas; Fristi Riandari (Institute of Computer Science (IOCS), 2019)
Cashew water is known by the Latin name Syzgiumaqueum. According to experts there are two subgroups taxonomy guava, guava fruit is small that the average acid (Syzygium aqueum) and large fruit guava and sweet (Syzqium samarangense). In terms of cultivation, handling guava honey was not easy. During this time the problem occurred in the field is the lack of knowledge of the owner of the types of pests and plant diseases guava honey so frequent misdiagnosis resulted in delays in menagani plant pests and diseases. In analyzing or diagnosing diseases in plants guava honey, the author uses the method Dempster Shafer. With the expert system analysis of the disease can help owners in knowing the disease and how to handle them. Dempster Shafer is a mathematical theory of evidence based belief functions and plausible reasoning (function beliefs and thoughts that makes sense) are used to combine separate pieces of information to calculate the probability of an event. Testing applications using the programming language PHP and MySQL database